Energy Conversion in Single‐Crystal‐to‐Single‐Crystal Phase Transition Materials. Issue 4 (28th April 2021) - Zheng, Yongshen; Jia, Xiaodi; Li, Kai; Xu, Jialiang; Bu, Xian‐He
Abstract: Single‐crystal‐to‐single‐crystal (SCSC) phase transitions are direct structural evolutions of crystalline materials in the solid state without the damage of ordering in the crystal lattice. These multidimensional SCSC phase transition materials are responsive to multiple external stimuli (heat, light, mechanical force, electricity, etc.), and have therefore demonstrated promising applications in many fields such as sensors, actuators, artificial muscles, soft robotics, and energy harvesting. The directionality and cooperativity of intermolecular interactions in crystal structures together with a sustained and long‐range dynamics, and the fact that they can operate at high frequency, enable fast and efficient energy conversion processes in SCSC phase transition materials. In this review, the SCSC phase transition materials are analyzed by dividing them into different types of energy transformation, from the point of view of different stimuli that initiate and drive the phase transition, including the thermo‐, photo‐, electric‐, and mechanic‐induced energy transformation, and the dimensionality dependent characteristics in these processes are presented. Moreover, the state‐of‐the‐art design and fabrication of the SCSC phase transition materials as well as the mechanisms of their energy conversion processes are discussed. Finally, the challenges and future potentials are also discussed. Abstract : Single‐crystal‐to‐single‐crystal (SCSC) phase transition materials serve as ideal platforms for energy conversion, because the directionality and cooperativity of intermolecular interactions in their structures enable fast and efficient energy conversion processes. These energy conversions with SCSC phase transition are categorized into thermo‐, photo‐, mechano‐, and electric‐induced energy conversion processes. The dimensionality dependent characteristics of SCSC phase transition in energy conversion processes are also highlighted.